Toward Quality of Education: Reviewing the Challenges of Quality Management in Primary School Contexts in Developing Countrie - Andriyanto, Andriyanto; Widodo, Joko (Universitas Negeri Semarang, 2025)
This study reviews the implementation challenges and strategic responses associated with educational quality management in Indonesian primary schools. As education systems increasingly adopt global quality frameworks such as Total Quality Management (TQM), ISO 21001, and the EFQM model, their alignment with national policy instruments, including the National Education Standards (SNP), Minimum Service Standards (SPM), and the 2024 Primary School Accreditation Framework—remains uneven. The research aims to identify key barriers in translating these frameworks into practical, sustainable quality assurance systems at the school level. Using a qualitative integrative literature review methodology, the study synthesizes findings from national regulations, international models, and peer-reviewed publications between 2015 and 2024. The analysis reveals five dominant challenges: fragmented governance, weak leadership capacity, limited teacher professionalism, inadequate infrastructure, and underutilized data systems. These issues not only hinder the fulfillment of national standards but also misalign with the global imperative for inclusive and continuous quality improvement. The study proposes strategic directions, including policy harmonization, leadership development, resource equity, and digital integration. Ultimately, the paper advocates a shift from compliance-oriented management to adaptive, stakeholder-driven improvement systems capable of supporting resilient and future-ready schools.